PENGGUNAAN MEDIA RODA BERPUTAR DALAM MENINGKATKAN PENGETAHUAN TENTANG PEMELIHARAAN KESEHATAN GIGI DAN MULUT SISWA SD KELAS V PANCUR BATU - Rawati Siregar; Sri Junita Nainggolan; Yetti Lusiani; Aminah br Saragih (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2024)
Dental and oral health problems can occur due to inadequate knowledge about oral and dental health maintenance techniques. Dessimination is an effort to increase knowledge of dental and oral health maintenance techniques using certain media, one of which is the spinning wheel game. This research is descriptive with a survey method, using a questionnaire, before and after dessimination, which aims to get an overview of dissimination, using a rotating wheel, on the level of knowledge of 30 grade 5 students regarding techniques for maintaining oral health at State Elementary School No. 101816 Pancur Batu. The results of the research show the level of knowledge of grade 5 students at State Elementary School No. 101816 Pancur Batu before and after dessimination by playing the spinning wheel: before dessimination, 10 students (33.3%) with good criteria, 16 students (53.3%) with medium criteria, and 4 students (13.4%) with bad criteria. and after dessimination, 23 students (76.7%) had good criteria, 7 students (23.3%) had medium criteria and none had bad criteria. This research concluded that there was an increase in students' knowledge after participating in the discussion by playing the spinning wheel. It is hoped that the dental and oral health team and schools educate students on maintaining oral health using media spin wheel games to increase elementary school students' knowledge.